2006
DOI: 10.1111/j.1744-7917.2006.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of Helicoverpa armigera (Hübner) and H. assulta (Guenée) (Lepidoptera: Noctuidae) based on AFLP markers

Abstract: Here we use amplified fragment length polymorphism (AFLP) to assess genetic differentiation of Helicoverpa armigera and H. assulta. The results indicated that both species‐specific fingerprints and cluster analysis showed the ability of AFLP technique to discriminate the two sibling species; among a total 1963 AFLP markers amplified from nine primer combinations: 777 (39.6%) were H. armigera‐specific, 602 (30.7%) were H. assulta‐specific, and 584 (29.7%) were common bands. The mean number of H. armigera‐specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Other rapid molecular methods that do not require sequencing have proven successful in separating H . armigera from other species of Helicoverpa present in the Old World [ 41 – 42 ]. Behere et al [ 18 ] developed a PCR-RFLP assay using two regions of mtDNA, COI, and cytochrome b (Cyt b ), to distinguish between H .…”
Section: Discussionmentioning
confidence: 99%
“…Other rapid molecular methods that do not require sequencing have proven successful in separating H . armigera from other species of Helicoverpa present in the Old World [ 41 – 42 ]. Behere et al [ 18 ] developed a PCR-RFLP assay using two regions of mtDNA, COI, and cytochrome b (Cyt b ), to distinguish between H .…”
Section: Discussionmentioning
confidence: 99%
“…H. armigera can be differentiated from H. punctigera based on a DNA-PCR of the ITS region (Pearce, 2003), allozyme electrophoresis (Daly & Gregg, 1985) and immunoassay (Trowell et al , 2000). Distinguishing between H. assulta and H. armigera is possible based on PCR-RFLP (Kranthi et al , 2005) and AFLP markers (Ming & Wang, 2006). Monoclonal antibodies raised against H. zea can distinguish, inter alia , H. armigera from H. punctigera (Greenstone et al , 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The H. armigera ‐specific DNA marker we developed allows a simple, fast and reliable discrimination between the two sister species of Helicoverpa . Compared with other diagnostic methods previously reported (Orui et al , 2000; Kranthi et al , 2005; Ming & Wang, 2006; Behere et al , 2008), the method reported here has the following advantages. First, it is very simple, consisting of only two straightforward steps (PCR amplification and electrophoresis separation), with no need for further treatment such as restriction enzyme digestion.…”
Section: Resultsmentioning
confidence: 80%
“…Although they have different host preferences, populations of these two species often occur in sympatry in China (Ming et al , 2007) owing to the common practice of intercropping agricultural systems (Wang et al , 2004; Wu et al , 2008). Moreover, the two insects are morphologically very similar, almost indistinguishable at the egg, larval and pupal stages, and only well‐trained entomologists can identify them by some morphological characteristics in the adult stage (Ming & Wang, 2006). These discriminable characters consist of slight differences of vein color in the forewing, different numbers of the diverticula on the basal pouch of everted vesicae, and some anatomical features of the adult genitalia (Matthews, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation